The role of HEMIS in the management of the educational system of higher education institutions - Ubaydullaeva Vasila Sadullaevna (Zien Journals, 2023)
The article analyzes the importance of digitalization and learning in the digital world in the HEMIS system of general secondary education and higher education in our country, current activities and opportunities.
Keywords: Distance education; digital technology; digitization